Lower Limb Arthroplasties in Colombia: Projections for 2050 Based on Official Records - Yesika Natali Fernández-Ortiz; Jorge Martín Rodríguez-Hernández (Epidemiologia)
Population ageing is driving a growing demand for orthopedic surgical procedures. The rise in chronic conditions such as osteoarthritis significantly contributes to disability among older adults, particularly women, and primarily affects the hip and knee joints, thereby increasing the need for arthroplasties. Objective: To determine the future demand for lower limb arthroplasty procedures among individuals aged 60 and over in Colombia up to 2050, using official public health records and national demographic projections. Methods: This study used an observational longitudinal retrospective design, using a Poisson regression model with official records from the Integrated Social Protection Information System—which consolidates procedures reported by both public and private healthcare service providers—to identify lower limb arthroplasties performed between 2015 and 2023. Population projections from the National Department of Statistics were incorporated to model future demand, accounting for demographic ageing and mortality trends. An additional analysis was conducted by sex and the most prevalent types of arthroplasties. Results: A total of 62,728 procedures took place from 2015 to 2023, with women undergoing approximately twice as many as men. The highest intervention rates occurred in the 65–69 and ≥80 age groups. By 2050, projections indicate the number of procedures will reach 39,270, with 52.7% projected among women. Conclusions: This study reports demographic trends in arthroplasties between 2015 and 2023 and offers insights into the anticipated future burden of lower limb arthroplasties among Colombia’s older population.